What are the migrants' contributions to employment and growth? A European approach - Rainer Münz; Thomas Straubhaar; Florin P. Vadean; Nadia Vadean (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2007)
The scope of this policy paper is to identify how the EU and its Member States could use availability and skills of today's and future immigrant populations in order to address economic and demographic challenges. To this end, it provides an analysis of the status quo and suggestions regarding future migration policies at both the Member States' level and at the EU level.
Keywords: 330